X-ray generation produced by relativistic electrons in compound "multifoil structure + crystal" targets; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 119, Iss. 1-2 - Andreyashkin M. Yu.; Kaplin V. V. Valeriy Viktorovich; Potylitsyn A. P. Alexander Petrovich; Uglov S. R. Sergey Romanovich; Zabaev V. N. Viktor Nikolaevich; Aramitsu K.; Endo I.; Goto K.; Horiguchi T.; Kobayashi T.; Takashima Y.; Muto M.; et al. (1996, 1996)
Title screen